(untitled) (Al-Farooq Journal of Sciences, 2026)
This study examined the role of excessive social media use in the mental health of female students at the Faculty of Education, Abu Issa, University of Zawia, from faculty members’ perspectives. It adopted a descriptive-analytical approach and used a 30-item questionnaire covering three dimensions. The questionnaire was administered to 50 faculty members from a population of 123. Results showed agreement that excessive use has a clear effect, with an overall mean of 3.78. Excessive-use manifestations ranked first with a mean of 3.83, while mental health indicators and academic and social interaction each recorded a mean of 3.75. A significant positive correlation was found between excessive social media use and mental health indicators (r = 0.682), as well as anxiety, tension, isolation, poor concentration, and reduced academic motivation. The study recommended awareness programs, time management, psychological counseling, and greater participation in direct university activities.